The rate of period change in pulsating DB white dwarf stars - Córsico, Alejandro Hugo (2004)
In this work, we present the theoretically expected rates of pulsation period change for V777 Her (DBV) variable stars. To this end we employ new evolutionary models representative of pulsating DB white dwarf stars computed in a self-consistent way with the predictions of time-dependent element diffusion. At the hot edge of the DB instability strip, the envelopes of the models are characterized by a diffusion-induced double-layered chemical structure. We compute the numerical values of rates of period change by solving the equations of linear, adiabatic, nonradial stellar oscillations. We examine the effects of varying the stellar mass, the mass of the helium envelope and the neutrino emission on the expected period changes. We present extensive tabulations of our results which could be useful for comparison with future detections of the rate of period change in pulsating DB white dwarfs.